2013
DOI: 10.1093/eurjhf/hfs214
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection criteria and midterm clinical outcome for MitraClip therapy in patients with severe mitral regurgitation and severe congestive heart failure

Abstract: AimsThe implantation of a MitraClip (MC) is a new treatment modality for severe mitral regurgitation (MR) in patients whose condition is inoperable or who are at high conventional operative risk. This study reports the follow-up data of patients implanted with an MC in our heart centre to find selection criteria for this procedure in patients with severe congestive heart failure. Methods and resultsThis study included 163 implantation procedures in 157 patients between March 2009 and November 2012. The severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 20 publications
5
55
0
1
Order By: Relevance
“…Further, left ventricular reverse remodeling has been demonstrated [9,15,29]. In those and various other studies [8,16,18,27,28], high-risk patients were identified by STS and Euroscore which predominantly contain factors characterizing the underlying cardiac disease such as previous cardiac surgery, LVEF, concomitant coronary artery disease and operative risk. However, the influence of noncardiac comorbidities on outcome has not been systematically assessed, neither in observational studies nor in the EVEREST II trial.…”
Section: Discussionmentioning
confidence: 96%
“…Further, left ventricular reverse remodeling has been demonstrated [9,15,29]. In those and various other studies [8,16,18,27,28], high-risk patients were identified by STS and Euroscore which predominantly contain factors characterizing the underlying cardiac disease such as previous cardiac surgery, LVEF, concomitant coronary artery disease and operative risk. However, the influence of noncardiac comorbidities on outcome has not been systematically assessed, neither in observational studies nor in the EVEREST II trial.…”
Section: Discussionmentioning
confidence: 96%
“…18,23,24) Plasma NT-pro BNP level is commonly increased in patients undergoing MC implantation, and preceding studies demonstrated that a higher baseline natriuretic peptide level was strongly associated with worse long-term outcomes after MC. 12,25) MC is attracting clinical interest as a therapeutic option for not only severe MR but also HF. Therefore, we were interested in the response of the plasma NT-pro BNP level, which reflects the change of HF status after MC.…”
Section: Discussionmentioning
confidence: 99%
“…9) Previous studies have reported that BNP had predictive value for MR patients, 10,11) and we previously reported that increasing NT-pro BNP levels were associated with worse outcomes in patients undergoing MC. 12) Mitral valve surgery decreased the serum BNP levels of MR patients. [13][14][15] However, little is known about the response of NT-pro BNP levels after MC implantation; therefore, the determinants of the NT-pro BNP response after this procedure still remain unknown.…”
mentioning
confidence: 95%
“…Several studies addressing this question have attempted to identify patients who will not derive benefit from MitraClip therapy. In Neuss and colleagues' [36] analysis of 157 patients with no surgical option or increased surgical risk because of poor left ventricular ejection fraction or comorbidities, mortality at 30 days after MitraClip was 7%, with 13% overall mortality at 6 months mainly because of severe, therapy-resistant endstage heart failure. Overall, 6% of patients needed surgery after MitraClip despite high operative risk because of persistent symptomatic mitral regurgitation.…”
Section: Evolving Criteria For Patient Selectionmentioning
confidence: 99%